PENINGKATAN HASIL BELAJAR BERDASARKAN MODEL PBL BERBASIS KOPIN PADA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Febriana Indah Nurcholish; Bambang Ismanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to determine the completeness of learning outcomes in Class IV science subjects using the PBL (Problem Based Learning) model based on Kopin (Spin Box). This classroom action research was motivated by the low learning outcomes of class IV students in science subjects. Data collection techniques use tests, observation and documentation. The data analysis techniques used are quantitative and qualitative. Quantitative analysis techniques use average formulas and classical learning completeness. Descriptive qualitative analysis technique for analyzing quantitative data in the form of student values ​​both from the process and results. The research subjects were class IV students at SD Negeri Noborejo 01 Salatiga with a total of 26 students. The results of the research show that the PBL (Problem Based Learning) model based on Kopin (Spin Box) is able to improve student learning outcomes in science learning. Students become conducive and enthusiastic in learning.